TAZAROTENE: A Concise Review of Mechanism of Action and Therapeutic Benefits: Pharmaceutical Science-Drug review - Khanna, Chahat; Sharma, Peeyush; Kaur, Simranjit; Singh, Sukhdeep; Rahar, Sandeep; Kumar, Lavish; Soni, Varinder; Kaur, Charanjeet; Kaur, Parminderjit; Kaur, Charanjit (International Journal of Life Science and Pharma Research, 2022)
Tazarotene is the first topical receptor-selective retinoid prodrug derived from vitamin A, used for managing plaque psoriasis, and effective in acne vulgaris, and photoaging. The aim and objective of writing this article were to recapitulate the information from the literature regarding every aspect of tazarotene, recent research including clinical trials and analytical methods of detection along with general characteristics uses and information about the physicochemical characteristics, pharmacokinetics properties, mechanisms of action, treatment strategies, dosage and administration, drug interactions, safety profile, potential for teratogenicity and, use in special populations like paediatrics and pregnant women. We have also mentioned the analytical methods like hyphenated and conventional chromatographic techniques such as LC–MS/MS and HPTLC, HPLC respectively used to estimate this drug both qualitatively and quantitatively in pharmaceutical formulations for quality control purposes. The clinical data considered in this study concludes the effect of tazarotene in psoriasis, acne vulgaris, and in the condition of brittle nails in different regimens, conditions, and dosage forms, providing good insights for clinicians. The data compiled in this review contain all the information related to tazarotene already published in the literature, but the scattered form and recent studies, including clinical trials, new composition of lotions as well as cream forms, were not mentioned in previous reviews. This review focussed on the updated use of tazarotene as a viable option for treating psoriasis and other skin conditions alone and in combination with corticosteroids or phototherapy as approved by regulatory bodies. Due to minimum side effects, convenient once-daily application, rapid and sustained response, tazarotene is an optimum choice for various diseased skin conditions in combination with a corticosteroid in the treatment of psoriasis than tazarotene alone, as per the literature and clinical data summarized in this article.